Trust me, I’m a computer? - Thimbleby, Harold (Future Healthc J, 2017)
Computers, IT, digitisation, apps – whatever we call it – is everywhere in healthcare, and it is also racing ahead of healthcare and creating dreams and exciting opportunities for quality improvement and transformation. We want a paperless NHS. Yet we have to be careful what we wish for. We are most familiar with consumer IT, our own personal phones and tablets, but our enthusiasm for this must not be confused with what might be best for healthcare.